TALENT MANAGEMENT AS A STRATEGIC DRIVER OF EMPLOYEE LOYALTY AND PRODUCTIVITY: A LITERATURE-BASED ANALYSIS (POLITEKNIK LP3I JAKARTA, 2026)
This study examines the strategic role of talent management in strengthening employee loyalty and productivity within the framework of Strategic Human Resource Management. Using a descriptive qualitative approach, this article applies a literature review method based on academic books, peer-reviewed journal articles, and relevant scientific publications on talent management, organizational commitment, employee engagement, and productivity. The data were analyzed through source selection, bibliographic verification, content analysis, and conceptual synthesis. The review suggests that talent management supports employee loyalty when recruitment, career development, performance management, rewards, organizational support, and work-life balance are aligned with employees' psychological commitment. Talent management also contributes to productivity through better person-job fit, continuous competency development, and stronger employee engagement. The article contributes theoretically by integrating talent management, employee engagement, loyalty, and productivity into a Strategic Human Resource Management-based conceptual framework. Practically, it offers guidance for HR practitioners in designing sustainable talent strategies without overstating quantitative effects beyond the reviewed literature.